The Effect Of ROA And FAR On Company Value With Dividend Policy As An Intervening Variable In Industrial Sector Companies Listed On The IDX - Wiwin Aklima; Edy Suryadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of ROA and FAR on Company Value with Dividend Policy as an Intervening Variable in Industrial Sector Companies Listed on the IDX. The number used in this study is the Industrial Sector Listed on the Indonesia Stock Exchange (IDX) in 2020-2022. This type of research is quantitative, secondary data, and purposive sampling. The technique used in collecting samples with multiple linear analysis using SPSS 19. The results of this study in equation 1 ROA and FAR have a significant effect on Company Value. And in equation 2 ROA, FAR, and Company Value partially do not affect dividend policy as an intervening variable.